2012
DOI: 10.1016/j.jcin.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Treatment of Coronary In-Stent Restenosis With a Paclitaxel-Coated Balloon Catheter

Abstract: Treatment of coronary ISR with paclitaxel-coated balloon catheters is safe and persistently reduces repeat revascularization during long-term follow-up. The initial results were sustained over the 5-year period. (Treatment of In-Stent Restenosis by Paclitaxel Coated PTCA Balloons [PACCOCATH ISR I]; NCT00106587. Treatment of In-Stent Restenosis by Paclitaxel Coated PTCA Balloons [PACCOCATH ISR II]; NCT00409981).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 215 publications
(96 citation statements)
references
References 24 publications
1
92
0
3
Order By: Relevance
“…Specifically, DCB compared to DES show a significant benefit in the treatment of ISR,5, 6, 7, 8, 9, 10, 11, 12 and current guidelines recommend the use of DCB for patients with coronary ISR (class I, level of evidence A) 13. However, there are other potential indications such as coronary small vessel disease and bifurcation lesions 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DCB compared to DES show a significant benefit in the treatment of ISR,5, 6, 7, 8, 9, 10, 11, 12 and current guidelines recommend the use of DCB for patients with coronary ISR (class I, level of evidence A) 13. However, there are other potential indications such as coronary small vessel disease and bifurcation lesions 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Over a period of up to 2 years, target lesion revascularization was performed in 21 of 54 patients treated with the uncoated balloons versus 3 of 54 patients treated with the coated balloons [74]. Meanwhile, longterm data up to 6 years confirms the initial finding with no signs of a late catch-up [75]. Subsequent trials compared a second-generation iopromide-matrix-coated PTCA catheter (SeQuent TM Please) with the Taxus™ stent in the treatment of bare metal stent restenosis (PEPCAD II [43]) or investigated the same device in drug-eluting stent restenosis [46,47] [48].…”
Section: üBersicht 353mentioning
confidence: 75%
“…Studies with at least 80% angiographic and 90% clinical follow-up were considered at low risk for attrition bias. On the basis of these criteria, the study by Scheller et al 29 and 3 other studies 21,25,30 were not considered low risk for attrition bias for clinical and angiographic end points, respectively. The risk of bias summary of the included studies is shown in Figure IV …”
Section: Study Quality Assessmentmentioning
confidence: 99%